Dreaming and the self : new perspectives on subjectivity, identity, and emotion - Mageo, Jeannette Marie, 1947- (SUNY series in dream studies., 2003)
"Drawing upon original fieldwork, cultural theory, and psychological research, Dreaming and the Self offers new approaches to the self - particularly to subjectivity, identity, and emotion. Through an investigation of dreams in various cultures, the contributors explore how people as subjects actually experience cultural life, how they forge identities out of their cultural and historical experiences, how the cultural and historical worlds in which they live shape even their bodily habits and responses, and how the person as agent responds to and imaginatively recreates his or her culture. These essays demonstrate that dreams reflect tellingly on topics of great currency in anthropology, such as how people personally manage postcolonialism, transnationalism, and migration."--Jacket